A survey of knowledge and attitudes towards antibiotic use and resistance among teachers in the Republic of Kenya: Implications for using teachers in raising public awareness of rational antibiotic use in school communities. - Patrick M Mutua; Joshua Mutiso; Michael M Gicheru (PLoS ONE)
Background Antimicrobial resistance is a significant public health threat. In Kenya, schools are targeted for public education to promote knowledge and attitudes towards the proper use of antimicrobials. However, there are limited studies that have investigated teachers' knowledge and attitudes on antibiotic use. Methods We conducted an online survey from December 2023 to January 2024 which included 608 primary and secondary school teachers, representing a response rate of 93% of the estimated sample size of 653 teachers. Data on the respondents' antibiotic knowledge score (seventeen questions) and attitude score (eleven questions) were analysed using IBM SPSS (Version 27). A binary logistic regression model was applied to analyze predicators of adequate knowledge and attitude on antibiotics. Results The average knowledge score for antibiotic use was 9.2 out of 17. Among the sampled teachers, 82% had not received public awareness information on proper antibiotic use. More than 86% of the respondents incorrectly answered that antibiotics are effective against colds. The average attitude score on antibiotic use was 6.1 out of 11. A quarter of the interviewees agreed that they gave family members antibiotics wherever they fell sick. Respondents aged 40-49 years and teaching in secondary school had higher odds for adequate knowledge in antibiotic use. Conclusions This study has identified significant knowledge and attitude gaps that need to be addressed by policy makers to ensure rational antibiotics use among teachers and in ensuring effective use of teachers in raising awareness in school communities for rational antibiotic use.